2006
DOI: 10.1111/j.1365-2605.2006.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of the biological variation of sperm DNA fragmentation in infertile men attending an andrology outpatient clinic

Abstract: Determination of sperm DNA fragmentation, as assessed by the sperm chromatin structure assay (SCSA), has become an important tool for the evaluation of semen quality. The aim of the present study was to describe the biological variation of sperm DNA fragmentation in men attending an andrology clinic and to identify clinical correlates of the biological variation of sperm DNA fragmentation. For this study, two consecutive semen samples from 100 patients attending our andrology outpatient clinic were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…Thus a primary defect in spermatogenesis can also result in oxidative stress. Impairment of sperm chromatin structure can be found to a variable degree in the majority of men with abnormal semen parameters, irrespective of the etiology of the semen abnormalities (6). Sperm DNA damage is probably the reflection of disrupted spermatogenesis due to several factors, including the presence of a varicocele.…”
Section: Pathophysiology Of Varicoceles With Focus On Oxidative Strementioning
confidence: 99%
See 1 more Smart Citation
“…Thus a primary defect in spermatogenesis can also result in oxidative stress. Impairment of sperm chromatin structure can be found to a variable degree in the majority of men with abnormal semen parameters, irrespective of the etiology of the semen abnormalities (6). Sperm DNA damage is probably the reflection of disrupted spermatogenesis due to several factors, including the presence of a varicocele.…”
Section: Pathophysiology Of Varicoceles With Focus On Oxidative Strementioning
confidence: 99%
“…Recently, studies have shown an increase in both reactive oxygen species (ROS) and apoptosis markers in semen of infertile men with a varicocele (5). Whether these substances play an etiologic role in the molecular mechanism by which varicoceles affect spermatogenesis is not clarified yet: they could simply be a consequence of defective spermatogenesis because they are also frequently found in semen of infertile men without a varicocele (6).…”
mentioning
confidence: 97%
“…It is suggested that this variability may explain the apparent different results when studies are compared. Sperm DNA fragmentation had a lower biological variability than classic semen parameters [Smit et al 2007]. It provides additional information about sperm quality and the ability of a couple to conceive.…”
Section: Discussionmentioning
confidence: 99%
“…SCSA based on flowcytometric method is a validated method for studying sperm DNA integrity [Evenson et al 1999]. Smit et al [2007] reported that the biological variation reported by the DFI is much lower than that of conventional semen parameters and DFI variability is not increased by varicocele. In the current study, we have shown that microsurgical repair is associated with a significant improvement over the classic semen parameters.…”
Section: Discussionmentioning
confidence: 99%
“…15,22,29,53,[62][63][64][65][66][67][68][69] In addition, sperm DNA damage is a more reliable outcome measure than sperm concentration or motility because measures of sperm DNA damage exhibit a lower degree of biological variability than conventional semen parameters. [70][71][72] Treatment with oral antioxidants has generally been associated with improvement in sperm DNA integrity and in some cases pregnancy rates after assisted reproduction, although most of these studies are small and few are randomized placebo-controlled trials ( Table 3).…”
Section: Relationship Between Oxidative Stress and Sperm Dysfunctionmentioning
confidence: 99%